Nanotechnology research methods for foods and bioproducts - Padua, Graciela W.; Wang, Qin, 1973- (Ames, Iowa : Wiley-Blackwell, 2012)
Food nanotechnology is an expanding field. This expansion is based on the advent of new technologies for nanostructure characterization, visualization, and construction. Nanotechnology Research Methods for Food and Bioproducts introduces the reader to a selection of the most widely used techniques in food and bioproducts nanotechnology. This book focuses on state-of-the-art equipment and contains a description of the essential tool kit of a nanotechnologist. Targeted at researchers and product development teams, this book serves as a quick reference and a guide in the selection of nanotechnolo.
Cover; Title page; Copyright page; Foreword; Contributors; 1 Introduction; 2 Material components for nanostructures; 2.1 Introduction; 2.2 Self-assembly; 2.3 Proteins and peptides; 2.4 Carbohydrates; 2.5 Protein-polysaccharides; 2.6 Liquid crystals; 2.7 Inorganic materials; 3 Self-assembled nanostructures; 3.1 Introduction; 3.2 Self-assembly; 3.3 Layer-by-layer assembly; 3.4 Nanoemulsions; 4 Nanocomposites; 4.1 Introduction; 4.2 Polymer nanocomposites; 4.3 Nanocomposite formation; 4.4 Structure characterization; 4.5 Biobased nanocomposites; 4.6 Conclusion.
Includes bibliographical references and index.
Print version record.
Keywords: Food -- Biotechnology; Nanotechnology; TECHNOLOGY & ENGINEERING -- Food Science; Food -- Biotechnology; Nanotechnology; Electronic books